1886 Md. Laws 315 - (:unkn) unknown (My University, 1886)
Ch. 189, § 1: Prohibited the carrying of a gun, pistol, dirk, dirk-knife, razor, billy or bludgeon on an election day. Punishable by a fine of $10-50.
Keywords: CARRY - CERTAIN PUBLIC PLACES